Two-Years Prospective Follow-Up Study of Subacute Thyroiditis - Zhao, Na; Wang, Shuo; Cui, Xue-Jiao; Huang, Ming-Shi; Wang, Shi-Wei; Li, Yu-Ge; Zhao, Lei; Wan, Wei-Na; Li, Yu-Shu; Shan, Zhong-Yan; Teng, Wei-Ping (Frontiers in Endocrinology, 2020)
Purpose: The aim of the present prospective follow-up study was to explore the early indicators of hypothyroidism and final changes in thyroid volume in subacute thyroiditis (SAT) patients. Methods: We enrolled 61 SAT patients and followed them for 2 years to assess the incidence of hypothyroidism and changes in thyroid volume. Binary logistic regression and receiver operating characteristic (ROC) curves were used for data analysis. Results: During the 2-year follow-up period, we found that the volume of the thyroid gland in SAT patients at 1 and 2 years was significantly smaller than that in the healthy control group, which was significantly smaller compared to the initial thyroid volume after SAT onset (p<0.001). Also the thyroid volume of SAT patients with hypothyroidism was significantly smaller than that of SAT patients without hypothyroidism. The early maximum thyroid stimulating hormone (TSH) value (within 3 months after SAT onset) was closely related to the incidence of hypothyroidism at 2 years. The OR value was 1.18 (95% CI 1.01-1.38, P=0.032). The early maximum TSH value had a maximum area under the ROC curve (AUC) of 0.866 for the development of hypothyroidism 2 years after SAT onset vs. euthyroidism (P<0.001). Conclusions: The thyroid volume of patients increased significantly after the onset of SAT, while during the follow-up the thyroid volume decreased and the thyroid volume at 1 and 2 years was significantly smaller than that of normal healthy subjects, especially in SAT patients with hypothyroidism. Furthermore, the early maximum TSH value could be used as effective indicators of the development of hypothyroidism 2 years after the onset of SAT.